CHARACTERISTICS OF SUPPLY CHAIN RISK MANAGEMENT CULTURE IN THE REPUBLIC OF SERBIA - Andjelković, Aleksandra (Economic Annals, 2017)
Supply chain risk management has become imperative. Therefore, needs for proactive supply chain risk management continuously is growing. Proactive supply chain risk management is not a great problem in developed countries. The problem is present in transition countries and underdeveloped countries. In those countries has not been built awareness about the importance of networking through supply chains and risk management within the supply chain. One of them is Republic of Serbia. Outside the door of the EU, the Republic of Serbia still retains the characteristics of the old system, and that is the great limitation for implementation of proactive supply chain risk management concept. Basic aim of paper is to research the level of proactive supply chain risk management. By using an adequate statistical methods, in paper will be analysed group of large enterprises from the Republic of Serbia. Besides that, author of paper suggesting the reasons and consequences of lack of proactive supply chain risk management.